Development of STEM-Integrated Problem-Based Learning Instructional Materials to Enhance Science Students’ Problem-Solving Ability - Masjudin Masjudin; Agus Muliadi; Ade Kurniawan; Fatwini Fatwini; Ita Chairun Nissa; Afturrizal Adaminata (Postgraduate, University of Mataram, 2022)
Mathematics education in Indonesia still faces challenges in developing students' Higher Order Thinking Skills (HOTS), particularly in mathematical problem-solving ability. One of the reasons for this is the limited availability of instructional materials specifically designed to support PBL-STEM. This study aims to develop Problem-Based Learning (PBL)-based mathematics instructional materials integrated with STEM to enhance the problem-solving abilities of science-stream students. This study is a Research and Development (R&D) project using the 4D model (Define, Design, Develop, and Disseminate). The subjects of this study consisted of 30 students from Grade 11 of SMAN 1 Labuhan Haji, who had low mathematical problem-solving skills. The developed materials included the Lesson Plan (RPP), Student Worksheet (LKS), problem-solving test, and practicality questionnaire for teachers. The results of validation by experts showed that the developed materials received an average score of 94.9%, which falls into the “highly valid” category. The practicality questionnaire, filled out by teachers, resulted in an average score of 92.5%, indicating that the materials are easy to use and well-structured. The effectiveness test, measured through a problem-solving test, showed an average N-Gain score of 0.72, which falls into the “high” category, indicating that the materials significantly improved students' problem-solving abilities. In conclusion, the PBL-STEM instructional materials developed in this study are valid, practical, and effective in enhancing the mathematical problem-solving ability of science-stream students.